Developing the promotion strategy of herbal tea: a study on Koperasi Pekebun Getah Negeri Melaka.Bhd / Nurul ’ Aifaa Yahaya - Yahaya, Nurul ’ Aifaa (Faculty of Business and Management, 2005)
This issues for this report is to knowing the “Effective Promotion Strategy Of Herbal Tea: A Study On Koperasi Pekebun Getah Negeri Melaka Bhd”. The reason for this issues was make is to analyze and identify what is the right promotional tools can be use to increase the promotional activities for the company to gain the profit , either the promotional strategy that was choosing is true or not. It also designed to help the marketing department of Koperasi Pekebun Getah Negeri Melaka Bhd to strategize and improve their activities of sales by promotion practional. The purpose for this study is to help marketing department for them to improve their promotional tools because all this while their promotional activities is weak. After reviewing related literature the data from the literiture has been summarized and from the finding its show that from collabrated with Coconut Gold Enterprise who produce the Virgin Coconut Oil and Multi Business Agrotech Sdn.Bhd that provide Leech cupping treatment is the effective promotion to succes.